Pengaruh Penerapan Prinsip 5C Dan Sistem Pengendalian Internal Terhadap Efektivitas Pemberian Kredit Pada Lembaga Pekreditan Desa (LPD) Di Kabupaten Gianyar - Ardani, Suti; Herawati, Nyoman Trisna (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to measure the 5C principles and the internal control system that provides credit. This research uses a quantitative approach, this study uses instruments in its measurement and processes it statistically and in the form of numbers. This research was conducted at LPDs in Gianyar Regency. The population in this study were 104 LPDs in Gianyar Regency which were divided into 3 districts. Sampling using the Slovin formula, in order to obtain a sample of 51 LPD. The research data were collected using a questionnaire which was then processed by multiple linear regression analysis with the help of SPSS version 22.The results of the study state that (1) the application of the 5C principle has a positive and significant effect on the effectiveness of credit extension. This shows that the better the application of the 5C principle, the more effective the provision of credit will be, and (2) the internal control system has a positive effect on the effectiveness of lending. This shows that the more effective the internal control system is, the higher the effectiveness of lending will be.